Satisfaction of HIV patients with task-shifted primary care service versus routine hospital service in northern Thailand - Aung, Myo Nyein; Moolphate, Saiyud; Kitajima, Tsutomu; Siriwarothai, Yaowaluk; Takamtha, Piyaporn; Katanyoo , Chitima; Okamura, Hiroshi; Field, Malcom; Noyama, Osamu; Wannakrairot, Pongsak; Klinbuayaem, Virat (The Journal of Infection in Developing Countries, 2015)
Introduction: Shifting the task of HIV care to primary care providers is an important strategy to sustain expanding access to antiretroviral therapy (ART) in high HIV burden countries like Thailand. In a pilot project, the task of following up ART-receiving patients was shifted from a physician-led HIV clinic team based at district level community hospital, to a nurse-led primary healthcare team of seven primary care centers, based at sub-district level in a district of Chiang Mai in northern Thailand. This study aimed to evaluate the task-shifted ART service in a patient-centered approach. Methodology: Patients’ satisfaction level was assessed cross-sectionally in a sample of 198 patients, which included 66 people living with HIV (PLHIV) receiving task-shifted ART service and matched controls in a ratio of 1:2. HIV immunological outcome was compared in a retrospective cohort of a year follow-up. Transculturally translated patient satisfaction questionnaire short form (PSQ-18) was used. Multivariate analysis of variance compared seven domains of patients’ satisfaction levels. Results: Community hospital patients expressed significantly higher levels of satisfaction with the technical quality, communication, and time spent by the service provider, whereas the task-shifted model patients experienced significantly better accessibility and convenience of the service. At the one-year follow up, CD4 counts of the two groups were not significantly different. Conclusion: Future research and training programs should aim to improve the technical quality and communication skills of nurse-led ART service teams to shift the task of HIV care and sustain expansion of ART access in primary care settings.